(untitled) (International Journal of Engineering and Computer Science, 2018)
Presenting here is an accelerometer based gesture controlled rover using PIC16F877, one of the most basic microcontroller. The robot can be moved in any direction just by making simple gestures, and the systems sensitivity to gestures can be easily adjusted as per our liking. The movement of gesture transmitter section is sensed by accelerometer and voltage level corresponds to movement of robot along X and Y axes are compared by a comparator, following which corresponding instructions are transmitted through the RF transmitter to control robot. The robot receives the instructions. The microcontroller drives motors corresponding to instructions received and displays the related message on LCD.